DeepFoG: An IMU-Based Detection of Freezing of Gait Episodes in Parkinson’s Disease Patients via Deep Learning - Bikias, Thomas; Iakovakis, Dimitrios; Hadjidimitriou, Stelios; Charisis, Vasileios; Hadjileontiadis, Leontios J. (Frontiers in Robotics and AI, 2021)
Freezing-of-Gait (FoG) is a movement disorder that mostly appears in the late stages of Parkinson's Disease (PD). It causes incapability of walking, despite the PD patient's intention, resulting in loss of coordination that increases the risk of falls and injuries, and severely affects PD patient's quality of life. Stress, emotional stimulus and multitasking have been encountered to be associated with appearance of FoG episodes, while patient's functionality and self-confidence are constantly deteriorating. This study suggests a non-invasive encountering of FoG episodes, by analyzing inertial measurement unit (IMU) data, towards a real-time intervention via a rhythmic auditory stimulation (RAS) and hand vibration. Specifically, accelerometer and gyroscope data from 11 PD subjects, as captured from a single wrist-worn IMU sensor during continuous walking, are processed via Deep Learning for window-based detection of the FoG events. The proposed approach, namely DeepFoG, was evaluated in a leave-one-subject-out (LOSO) cross-validation (CV) and 10-fold CV fashion schemes against its ability to correctly estimate the existence or not of a FoG episode at each data window. Experimental results have shown that DeepFoG performs satisfactorily, as it achieves 83%/88% and 86%/90% sensitivity/specificity, for LOSO CV and 10-fold CV schemes, respectively. The promising performance of the proposed DeepFoG reveals the potentiality of single-arm IMU-based real-time FoG detection that could guide effective interventions via stimuli, such as RAS and hand vibration. In this way, DeepFoG scaffolds the elimination of risk of falls in PD patients, sustaining their quality of life in everyday living activities.